2015
DOI: 10.1371/journal.pone.0116197
|View full text |Cite
|
Sign up to set email alerts
|

Regulation and Methylation of Tumor Suppressor MiR-124 by Androgen Receptor in Prostate Cancer Cells

Abstract: Prostate cancer (PCa) is the most frequently diagnosed cancer for men in the developed world. Androgen receptor signaling pathway plays an important role in prostate cancer progression. Recent studies show that microRNA miR-124 exerts a tumor suppressive function in prostate cancer. However, the relationship between AR and miR-124 is unclear. In the present study, we found a negative feedback loop between AR and miR-124 expression. On one hand, miR-124 was a positively regulated target gene of the AR, on the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 28 publications
(40 reference statements)
0
16
0
Order By: Relevance
“…Thus far, several miRNAs are previously reported to be dysregulated in liver cancer, including miR-21, miR-122, miR-181b, miR-338, and miR-491 (12)(13)(14)(15)(16), which are all closely associated with the migration and metastasis of liver cancer. miR-124a functions as a tumour suppressor in osteosarcoma, endometrial carcinoma, prostate cancer, and glioblastoma (17)(18)(19)(20). It is also downregulated in liver cancer tissues (21).…”
Section: Introductionmentioning
confidence: 99%
“…Thus far, several miRNAs are previously reported to be dysregulated in liver cancer, including miR-21, miR-122, miR-181b, miR-338, and miR-491 (12)(13)(14)(15)(16), which are all closely associated with the migration and metastasis of liver cancer. miR-124a functions as a tumour suppressor in osteosarcoma, endometrial carcinoma, prostate cancer, and glioblastoma (17)(18)(19)(20). It is also downregulated in liver cancer tissues (21).…”
Section: Introductionmentioning
confidence: 99%
“…Alterations in miR promoter DNA methylation levels have been demonstrated to modulate the abundance of miRs. 26,27 Interestingly, in multiple tumors, including hepatocellular carcinoma, 28 stomach adenocarcinoma, 29 and prostate cancer, 30 it has been shown that miR-124 levels rely strongly on the DNA methylation of its promoter. Downregulation of miR-124 in these tumors promoted their metastasis and/or development.…”
Section: Introductionmentioning
confidence: 99%
“…Also although miR-124 inhibited AR expression, miR-124 was positively regulated by AR, suggesting a negative feedback loop between the AR and miR-124, controlling the progression of CRPC (Shi et al 2013, Chu et al 2015. miRNAs associated with cell cycle and apoptosis in PCa miRNAs play a critical role in PCa through modulation of protein expression involved in cell cycle regulation and apoptosis, such as p53, Bcl2/Bcl-xl, E2F, cyclins, CDKs, among others (see box 3 for related terminology, Fig.…”
Section: Mir-124mentioning
confidence: 99%